Dissemination of Computer Music Theory outside academia - Porres, Alexandre Torres (My University, 2010)
This UnConference topic discusses the Dissemination of Computer Music Theory outside academia like: what factors helped to promote it? what are the consequences and impact outside and inside academia? And what can we expect to happen in the near future? The issues raised should make us think on how to engage ourselves in this process of renewal and change that is being taken place.